Palladium‐Catalyzed Chemoselective and Biocompatible Functionalization of Cysteine‐Containing Molecules at Room Temperature. Issue 32 (30th June 2016) - Al‐Shuaeeb, Riyadh Ahmed Atto; Kolodych, Sergii; Koniev, Oleksandr; Delacroix, Sébastien; Erb, Stéphane; Nicolaÿ, Stéphanie; Cintrat, Jean‐Christophe; Brion, Jean‐Daniel; Cianférani, Sarah; Alami, Mouâd; Wagner, Alain; Messaoudi, Samir
Abstract: The third generation of aminobiphenyl palladacycle pre‐catalyst "G3‐Xantphos" enables functionalization of peptides containing cysteine in high yields. The conjugation (bioconjugation) occurs chemoselectively at room temperature under biocompatible conditions. Extension of the method to protein functionalization allows selective bioconjugation of the trastuzumab antibody. Abstract : The third generation of aminobiphenyl palladacycle pre‐catalyst "G3‐Xantphos" enables the functionalization of peptides containing cysteine in high yields. The bioconjugation occurs chemoselectively at room temperature under biocompatible conditions. (see figure).